2017
DOI: 10.1515/amm-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Formation of microstructure and properties of Cu-3Ti alloy in thermal and thermomechanical processes

Abstract: This paper presents the possibilities of forming the microstructure as well as mechanical properties and electrical conductivity of Cu-3Ti alloy (wt.%) in thermal and thermomechanical processes that are a combination of homogenising treatment, hot and cold working, solution treatment and ageing. Phase composition of the alloy following various stages of processing it into the specified semi-finished product was being determined too. It was demonstrated that the application of cold plastic deformation between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…The hardness results are in accordance with the behavior observed by previous investigations where the titanium increase had a positive effect on the hardness value, especially in values higher than 5% [8,42,48]. The studies carried out by Akbarpour et al [20] present a close reference to the hardness values found in the composites, despite the need for an aging process in order to promote intermetallic growth and the elimination of the thermal stress of the sintering to the extent that ideal values proposed by Shon et al [49].…”
Section: Microhardness Of the Materialsupporting
confidence: 91%
“…The hardness results are in accordance with the behavior observed by previous investigations where the titanium increase had a positive effect on the hardness value, especially in values higher than 5% [8,42,48]. The studies carried out by Akbarpour et al [20] present a close reference to the hardness values found in the composites, despite the need for an aging process in order to promote intermetallic growth and the elimination of the thermal stress of the sintering to the extent that ideal values proposed by Shon et al [49].…”
Section: Microhardness Of the Materialsupporting
confidence: 91%
“…Solution treated process resulted in hardness reduction of the alloy from 171 Hv5 to 85 Hv5 after homogenization. in the study of Szkliniarz for the Cu-3Ti alloy, this value resulted in a decrease from 163 Hv10 to 103 Hv10 with the solution treated after homogenization [8]. The solution treatment of titanium bronzes usually takes place at about 900°C.…”
Section: Hardness Measurements and Microstructure Characterizationmentioning
confidence: 99%
“…The solution treatment of titanium bronzes usually takes place at about 900°C. Thus, small Cu and Ti intermetallic precipitates remain in the microstructure after the homogenization process is dissolved [1,8,[12][13][14][15][16]. for the applications in engineering and investigating fundamental aspects of hardening phenomena in Cu-Ti alloy system, the decomposition during aging between 300º and 500ºC is understood well including spinodal decomposition, with compositional fluctuations, formation of a coherent, metastable phase called β' and equilibrium phase β by a discontinuous or cellular reaction [14][15][16].…”
Section: Hardness Measurements and Microstructure Characterizationmentioning
confidence: 99%
See 2 more Smart Citations